Orange is the new black [large type] : my year in a woman's prison - Kerman, Piper (Thorndike Press, 2014)
This is a compelling, often hilarious, and unfailingly compassionate portrait of life inside a women's prison. With a career, a boyfriend, and a loving family, the author barely resembles the reckless young woman who delivered a suitcase of drug money ten years before. But that past has caught up with her. Convicted and sentenced to fifteen months at the infamous federal correctional facility in Danbury, Connecticut, the well-heeled Smith College alumna is now inmate #11187-424, one of the millions of people who disappear "down the rabbit hole" of the American penal system. From her first strip search to her final release, she learns to navigate this strange world with its strictly enforced codes of behavior and arbitrary rules. She meets women from all walks of life, who surprise her with small tokens of generosity, hard words of wisdom, and simple acts of acceptance.